2012
DOI: 10.1017/s1355617712001105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Semantic Dementia on Everyday Actions: Evidence from an Ecological Study

Abstract: In theory, semantic memory may trigger and support the execution of everyday activities. This study explored this question by comparing three patients with semantic dementia to 40 normal controls performing different everyday activities. Participants were tested in their home using the Instrumental Activities of Daily Living Profile, an ecological measure of everyday functioning. Participants were informed that they had unknowingly invited two guests for lunch and should prepare accordingly. With these instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…These results need to be set against the relative independence of SD patients in activities of daily living, despite their massive semantic deficit (Bier et al, 2013;Bier and Macoir, 2010). This relative independence is quite astonishing, given that in other degenerative diseases (including AD), functional disorders hamper everyday life at a far earlier stage in the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…These results need to be set against the relative independence of SD patients in activities of daily living, despite their massive semantic deficit (Bier et al, 2013;Bier and Macoir, 2010). This relative independence is quite astonishing, given that in other degenerative diseases (including AD), functional disorders hamper everyday life at a far earlier stage in the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown how different basic ADLs deteriorate throughout the stages 11,17,21 , with bathing, dressing, and continence for example deteriorating early on. Although IADLs are known to deteriorate largely in the early stages of the disease 31 , comprehensive knowledge on the components of IADLs (initiative and performance) and their decline has been very limited to date 19,20,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…As with the majority of the literature however, the authors failed to describe the level of decline for individual activities, which is crucial for exploring the cognitive underpinnings and for developing effective interventions . In a more ecological approach involving direct observation Bier et al (2013) rated the performance of dressing, orientation and transport (to the grocery store), shopping, preparing a hot meal and cleaning up in SD. Whilst grocery shopping and hot meal preparation were impaired the most, dressing did not represent a problem.…”
Section: Functional Problems In Early Dementiamentioning
confidence: 99%